Feasibility of ultrasonic waves to improve mass transfer rate during osmotic dehydration of seedless guava (Psidium guajava L.) - Ganjloo, Ali; Abdul Rahman, Russly; Bakar, Jamilah; Osman, Azizah; Bimakr, Mandana (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Osmotic dehydration is a viable process for the partial removal of water in which cellular materials are placed in a concentrated solution of soluble solute. The initial results showed that the values of mass transfer terms (0.2 (g/g) water loss and 0.03 (g/g) solid gain) at the studied range of process variables including temperature of 33 ºC, sucrose concentration of 30% w/w and 180 min of immersion time were not in accordance with an efficient osmotic dehydration process which 40–60% water loss and <10% solid gain are mostly aimed. Thus, feasibility of ultrasonic wave in order to improve the rate of mass transfer was investigated. Ultrasonic treatment was carried out with 20 kHz frequency in the amplitude range of 25-75% for different lengths of sonication time (10-30 min). The highest amounts of water loss (0.42 (g/g)) and solid gain (0.073 (g/g)) were obtained by application of ultrasonic treatment. These increases can be attributed to increased cell wall permeability, facilitating transport of water and solute, as evidenced by the excess conductivity of ultrasonically treated samples as compared with a control condition. The results revealed that ultrasonic technology can be carried out to improve rate of mass transfer during osmotic dehydration.